Pengaruh Bakteriosin Produksi Bakteri Asam Laktat Isolat Indonesia terhadap Jumlah Bakteri dalam Susu Pasteurisasi - Nurliana Nurliana; Idwan Sudirman; Mirnawati Sudarwanto; Raden Roso Soejoedono (Agricultural Faculty, 2009)
The effect of bacteriocin produced by Indonesia Isolate of lactic acid bacteria toward total bacteria in pasteurized milkABSTRACT. The aim of this research was to study the ability of bacteriocin (amylocin) produced by Indonesian isolate of Lactic Acid Bacteria (LAB) (Lactobacillus amylovorus US 121) and its combination with nisin in pasteurized milk. The total bacteria was measured by plate count method. The antimicrobial activity of amylosin at 64 AU/ml had the same activity with nisin at 625 AU/ml and its combination between amylosin and nisin at 32 AU/ml and 312,5 AU/ml respectively against psychrotrophic, thermoduric bacteria and L. monocytogenes in pasteurized milk. However, combination of amylosin and nisin (32 AU/ml + 312,5 AU/ml) able to reduce S. aureus in pasteurized milk. Amylosin at 64 AU/ml kept the shelf life of pasteurized milk longer until 12 days at 10oC. The addition of amylosin (the precipitate resulted by ammonium sulfate precipitation at 70% w/v) changed the color of pasteurized milk be brownish white.